Highly‐Efficient Solar Steam Generation with Real Time Salinity Monitoring for Seawater Desalination. (29th December 2021) - Xiong, Meiyu; Dong, Suwei; Xu, Yunfan; Liu, Cihui; Di, Yunsong; Xing, Fangjian; Wu, Shuyi; Zhang, Jinlei; Yu, Liyan; Dong, Lifeng; Gan, Zhixing
Abstract: Solar steam generation (SSG) has attracted increasing interest due to its huge potential in seawater desalination. However, SSG performance is not yet satisfactory due to limited photothermal efficiency and crude thermal management. In addition, real‐time salinity monitoring is still lacking. Herein, inspired by the transpiration of trees, an umbrella‐shaped 3D structure is designed for high‐performance SSG. The water evaporation rate under one sun irradiation is as high as 2.17 kg m −2 h −1, outcompeting most previous work. The high evaporation rate is primarily attributed to the excellent photothermal effect and maximized utilization of the heat via enhancing water transport and enlarging the effective evaporation area. Due to the existence of an air gap between the umbrella cover and the bulk water, an extra thermal insulator is not needed. Thus, the SSG device is more compact and stable. Moreover, a flexible photonic crystal membrane is constructed to in situ monitor the salinity by the structural color via a visualization method. This SSG device keeps high evaporation rates in seawater desalination, showing great prospects for practical applications. Abstract : Inspired by the transpiration of trees, an umbrella‐shaped 3D origami design is used for highly efficient solar steam generation. The water evaporation rate under one sun irradiation is as high as 2.17 kg m −2 h −1 . Moreover, a flexible photonic crystal membrane is constructed to in situ monitor the salinity by the structural color via a visualization method.